Kompetensi dan Indepedensi Auditor dalam Kualitas Audit : Survey pada Auditor Inspektorat Kabupaten Pinrang: - - Khaeril; Firmansyah, Fajar (Insan Cita Bongaya Research Journal, 2025)
Abstract. This study aims to test and analyze the influence of auditor competence and independence on audit quality. The survey was carried out on the Government Internal Supervisory Apparatus (APIP), namely the auditor of the Pinrang Regency regional inspectorate. Sample withdrawal used the saturated sample technique, so that the total sample was 63 auditors. Data collection used the saturated sample technique. Data analysis used multiple regression analysis techniques. The results of the study show that auditor competence has a significant positive effect on audit quality. Meanwhile, the independence of the auditor has no effect on the quality of the audit. Keywords: Competence, Independence, Auditor, Audit quality